Pengaruh debt to equity ratio (der), return on investment (roi), kepemilikan manajerial dan ukuran perusahaan terhadap dividen per share (dps) pada perusahaan manufaktur yang terdaftar di bursa efek indonesia (bei) - Wan Aulia Ikhsan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to determine the effect of Debt to Equity Ratio, Return on Investment, Managerial Ownership and Company Size toward Dividend Per Share of manufacturing companies listed on the Indonesia’s Stock Exchange. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2008-2010. The sample in this study was determined by purposive random sampling method based on the some criteria. Manufacturing companies listed in Indonesia Stock Exchange by the end of 2010 was 146 companies, while the companies that meet the criteria of a sample of 39 companies. To analyzed data was use multiple regression model. According to this study result, the independent variables namely the Debt to Equity Ratio , Return on Investment , and Firm Size partially have a significant effect to the Dividend Per Share, while the managerial ownership has no significant effect to the Dividend Per Share of the manufacturing companies listed on the Stock Exchange 2008-2010 .Based on Adj R Square shows the value of 0.600 . This indicates that 60.00 % of DPS changes influenced by determinant variables in the model while the remaining 40 % is explained by other variables not included in the model .Keywords : Debt to Equity Ratio, Return On Investment, Company Size, Dividend Per Share, Managerial Ownership